Development of a brief, reliable and valid diet assessment tool for impaired glucose tolerance and diabetes: the UK Diabetes and Diet Questionnaire. Issue 2 (9th September 2016) - England, Clare Y; Thompson, Janice L; Jago, Russ; Cooper, Ashley R; Andrews, Rob C
Abstract: Objective: Dietary advice is fundamental in the prevention and management of type 2 diabetes (T2DM). Advice is improved by individual assessment but existing methods are time-consuming and require expertise. We developed a twenty-five-item questionnaire, the UK Diabetes and Diet Questionnaire (UKDDQ), for quick assessment of an individual's diet. The present study examined the UKDDQ's repeatability and relative validity compared with 4 d food diaries. Design: The UKDDQ was completed twice with a median 3 d gap (interquartile range=1–7 d) between tests. A 4 d food diary was completed after the second UKDDQ. Diaries were analysed and food groups were mapped on to the UKDDQ. Absolute agreement between total scores was examined using intra-class correlation (ICC). Agreement for individual items was tested with Cohen's weighted kappa ( κ w ). Setting: South West of England. Subjects: Adults ( n 177, 50·3 % women) with, or at high risk for, T2DM; mean age 55·8 (sd 8·6) years, mean BMI 34·4 (sd 7·3) kg/m 2 ; participants were 91 % White British. Results: The UKDDQ showed excellent repeatability (ICC=0·90 (0·82, 0·94)). For individual items, κ w ranged from 0·43 ('savoury pastries') to 0·87 ('vegetables'). Total scores from the UKDDQ and food diaries compared well (ICC=0·54 (0·27, 0·70)). Agreement for individual items varied and was good for 'alcohol' ( κ w =0·71) and 'breakfast cereals' ( κ w =0·70), with no agreement for 'vegetables' ( κ w =0·08) or 'savoury pastries' ( κ w =0·09). Conclusions: The UKDDQ is a new British dietary questionnaire with excellent repeatability. Comparisons with food diaries found agreements similar to those for international dietary questionnaires currently in use. It targets foods and habits important in diabetes prevention and management.